A Gratitude from the Perspective of Students’ Organizational Culture: A Study of IMM and PMII Members in South Sulawesi, Indonesia - Mutmainnah, Mutmainnah; Syamsu Yusuf; Hafina, Anne; Saripah, Ipah; Asbar, Asbar; Masnur, Masnur; Mustakim, Mustakim (Universitas Negeri Padang, 2025)
This study examines the dynamics of student gratitude from the perspective of organizational culture within two prominent Islamic student organizations in South Sulawesi: IMM (Indonesian Muhammadiyah Student Association) and PMII (Indonesian Muslim Students Movement). Gratitude, as a vital attitude and value, is explored through the lens of organizational culture, which shapes how gratitude is expressed and internalized within these organizations. The research employed a saturated sampling method, involving 530 active students who held leadership or committee roles during the 2022-2023 period. Participants were selected from seven universities in South Sulawesi. Data were categorized into three levels of gratitude: low, moderate, and high. To gain deeper insights, virtual group discussions (VGD) were conducted with 6 participants, representing various levels of gratitude. The study's findings suggest that organizational culture in IMM and PMII plays a significant role in fostering gratitude, with members demonstrating appreciation through acts of kindness, volunteerism, and community service. The integration of religious and cultural values in the organizational practices of both IMM and PMII enhances the sense of collective responsibility. It supports the development of responsible, empathetic, and socially engaged citizens. This research contributes to understanding how gratitude, as a personal and collective virtue, can be cultivated within the framework of organizational culture, promoting social justice, inclusion, and the holistic development of students. The findings provide valuable insights for the development of guidance and counseling models that focus on enhancing students' gratitude in academic settings.